Large herbivores change the direction of interactions within plant communities along a salt marsh stress gradient. (24th June 2015) - Howison, Ruth A.; Olff, Han; Steever, Rutger; Smit, Christian; Bartha, Sándor
Abstract Question How multiple abiotic stress factors combined with herbivory affect interactions within plant communities is poorly understood. We ask how large herbivore grazing affects the direction of plant–plant interactions along an environmental gradient in a salt marsh. Location Grazed (cattle) and ungrazed salt marshes of the Dutch Wadden Sea island Schiermonnikoog. Here, patches of tall plant communities, dominated by the tough, unpalatable species Juncus maritimus Lam., are found alternating with low‐statured, intensively grazed plant communities. Methods Along the inundation gradient, we measured plant species composition and plant species traits (specific leaf area, specific root length, maximum height and abundance) inside and outside J. maritimus patches in grazed and ungrazed areas. In addition, we measured soil structure parameters (bulk density, soil porosity, clay depth), multiple limiting conditions for plant growth (soil salinity, soil redox, plant canopy light interception), plant biomass, presence of herbivores and abundance of soil macro‐detritivores. Results Under grazing, the palatable grasses Elytrigia atherica (Link) Kerguélen and Festuca rubra L. were positively associated with J. maritimus, while shade‐intolerant Puccinellia maritima (Huds.) Parl. and Juncus gerardii Loisel. were negatively associated with this species. Furthermore, macro‐detritivore presence was higher inside J. maritimus patches. In ungrazed areas E. atherica and F. rubra were negatively associated with J. maritimus, while P. maritima and J. gerardii were rare. In both grazed and ungrazed conditions the directions of species associations were independent of the inundation gradient. Analysis of species traits and abiotic conditions suggested that associational resistance (a facilitation type) was important in grazed areas. In ungrazed areas, light competition was the likely dominant process. Conclusions The direction of species associations within these salt marsh communities was strongly affected by grazing, not by the underlying stress gradient. Measurement of species traits indicated that plant–plant interactions shifted from competitive to facilitative under grazing. Besides grazing, cross‐trophic facilitation of soil disturbing macro‐detritivores may play an important – thus far ignored – role in structuring plant communities.